Valdosta High School Scrapbook 15, January 1972 – August 1972 - Valdosta High School (My University, 1972)
This item is a collection of newspaper articles talking about Valdosta High School. In these articles the basketball season is currently ongoing for both men's and women's basketball.
This item contains 1 PDF file with 108 pages and a title page.
Keywords: Newspapers; Photographs; Scrapbooks; Lowndes County (Ga.)